(untitled) (Journal of Atomic, Molecular, Condensed Matter and Nano Physics, 2018)
The developments in the field of electrically conducting polymers have grown very rapidly since the discovery and there is a very sharp increase in conductivity when intrinsically insulating organic conjugated polymers are doped with oxidizing and reducing agents. An overview of technological developments involving conducting polymers clearly indicates that the field expands at unprecedented rates. The manuscript first introduces the conducting polymers (CPs), conducting mechanism, concepts of doing and briefly introduces main applications. Different types of CPs, their unique properties and synthesis is discussed. The present review will help the effective implementation of conducting polymers in different fields, which directly depends on the degree of understanding of their behaviour and properties.